2021
DOI: 10.1111/maec.12646
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic diversity of culturable marine bacteria from sediments underlying the oxygen minimum zone of the Arabian Sea and their role in nitrate reduction

Abstract: The dissolved oxygen concentration in ocean water is the main driver of nutrient and energy flow patterns within marine ecosystems (Diaz & Rosenberg, 2008;Diaz et al., 2009). Oxygen deficiency in ocean water selects for microbial groups capable of utilizing alternative respiratory substrates including nitrate, nitrite, sulfate, or carbon dioxide (Zehnder & Stumm, 1988). Within oxygen-deficient waters, the use of nitrite or nitrate as alternative electron acceptors results in the production of nitrous oxide and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
(90 reference statements)
2
5
0
Order By: Relevance
“…Previous studies have consistently identified the phyla Proteobacteria, Firmicutes, and Actinobacteria as the predominant bacterial groups in this region. This finding further supports the notion that these phyla play a crucial role in shaping the bacterial composition and dynamics within the productive upwelling zone of the Arabian Sea (Amberkar et al 2021;Parab et al 2022). Firmicutes contributed maximum during the monsoon season showing an abundance of 71% each in both water and sediment.…”
Section: Variation In the Diversity Of Bacterial Morphotypes Isolated...supporting
confidence: 86%
“…Previous studies have consistently identified the phyla Proteobacteria, Firmicutes, and Actinobacteria as the predominant bacterial groups in this region. This finding further supports the notion that these phyla play a crucial role in shaping the bacterial composition and dynamics within the productive upwelling zone of the Arabian Sea (Amberkar et al 2021;Parab et al 2022). Firmicutes contributed maximum during the monsoon season showing an abundance of 71% each in both water and sediment.…”
Section: Variation In the Diversity Of Bacterial Morphotypes Isolated...supporting
confidence: 86%
“…Proteobacteria have been identified as the dominant phylum and play a significant role in denitrification in the AS-OMZ (Bandekar et al, 2018a;Gomes et al, 2018). OTUs obtained from the ASTS aligned into three classes: Alphaproteobacteria, Betaproteobacteria, and Gammaproteobacteria, which is consistent with findings from the OMZ of the Subtropical Deep Reservoir (Zheng et al, 2014) and sediments of the AS (Amberkar et al, 2021). nosZ denitrifiers from the present study were predominant within the class Alphaproteobacteria, which is in accordance with the findings of Wyman et al (2013) from the AS.…”
Section: The Nosz Phylogenysupporting
confidence: 81%
“…The redox conditions of OMZs are often favorable for processes in the nitrogen cycle such as denitrification and anammox as well as other important processes in the sulfur and methane cycles. These redox conditions are reflected in the organisms present in OMZs such as known nitrogen and sulfur cycling organisms like genera belonging to Candidatus Scalindua, Caulobacteriaceae, Pelagibacteriaceae, α-Proteobacteria, δ-Proteobacteria, and γ-Proteobacteria in the Arabian Sea and Bay of Bengal (Bandekar et al, 2018a,b;Rajpathak et al, 2018;Fernandes et al, 2019Fernandes et al, , 2020Amberkar et al, 2021), the Gulf of Alaska (Muck et al, 2019), Cariaco Basin (Madrid et al, 2001;Lin et al, 2008;Rodriguez-Mora et al, 2013Cernadas-Martín et al, 2017), the ETSP (Stevens and Ulloa, 2008;Bryant et al, 2012), the ETNP (Podlaska et al, 2012;Beman and Carolan, 2013;Beman et al, 2020;Pajares et al, 2020), and Saanich Inlet (Zaikova et al, 2010;Walsh and Hallam, 2011;Torres-Beltrán et al, 2019). The contribution of prokaryotes identified in OMZs to biogeochemical cycles has global ramifications and has thus been well-studied throughout previous decades and remains a highly active research endeavor.…”
Section: Prokaryotesmentioning
confidence: 99%
“…The role of sediments in nutrient cycling extends to the nitrogen cycle as nitrification, denitrification, anammox, and DNRA all occur in the ETSP, where the sediments contribute to a net loss of N where the bottom waters are anoxic or nearly anoxic (Bohlen et al, 2011). Denitrifiers are also found in the sediments underlying the Arabian Sea (Lincy and Manohar, 2020;Amberkar et al, 2021), the Bay of Bengal (Lincy and Manohar, 2020), and the ETNP (Liu et al, 2003). Even the sediments in less intense OMZs, such as the NESAP, can greatly contribute to N 2 O production from denitrification and is largely modulated by the oxygen concentration of bottom waters (Jameson et al, 2021).…”
Section: Sedimentsmentioning
confidence: 99%
See 1 more Smart Citation